Overall survival benefit with tebentafusp in metastatic uveal melanoma - Nathan, Paul; Hassel, Jessica C.; Rutkowski, Piotr; Baurain, Jean-Francois; Butler, Marcus O.; Schlaak, Max; Sullivan, Ryan J.; Ochsenreither, Sebastian; Dummer, Reinhard; Kirkwood, John M.; Joshua, Anthony M.; Sacco, Joseph J.; et al. (The New England journal of medicine)
BACKGROUND Uveal melanoma is a disease that is distinct from cutaneous melanoma, with a low tumor mutational burden and a 1-year overall survival of approximately 50% in patients with metastatic uveal melanoma. Data showing a proven overall survival benefit with a systemic treatment are lacking. Tebentafusp is a bispecific protein consisting of an affinity-enhanced T-cell receptor fused to an anti-CD3 effector that can redirect T cells to target glycoprotein 100-positive cells. - METHODS In this open-label, phase 3 trial, we randomly assigned previously untreated HLAA*02:01-positive patients with metastatic uveal melanoma in a 2:1 ratio to receive tebentafusp (tebentafusp group) or the investigator’s choice of therapy with singleagent pembrolizumab, ipilimumab, or dacarbazine (control group), stratified according to the lactate dehydrogenase level. The primary end point was overall survival. - RESULTS A total of 378 patients were randomly assigned to either the tebentafusp group (252 patients) or the control group (126 patients). Overall survival at 1 year was 73% in the tebentafusp group and 59% in the control group (hazard ratio for death, 0.51; 95% confidence interval [CI], 0.37 to 0.71; P<0.001) in the intentionto-treat population. Progression-free survival was also significantly higher in the tebentafusp group than in the control group (31% vs. 19% at 6 months; hazard ratio for disease progression or death, 0.73; 95% CI, 0.58 to 0.94; P = 0.01). The most common treatment-related adverse events in the tebentafusp group were cytokine-mediated events (due to T-cell activation) and skin-related events (due to glycoprotein 100-positive melanocytes), including rash (83%), pyrexia (76%), and pruritus (69%). These adverse events decreased in incidence and severity after the first three or four doses and infrequently led to discontinuation of the trial treatment (2%). No treatment-related deaths were reported. 1196 - CONCLUSIONS Treatment with tebentafusp resulted in longer overall survival than the control therapy among previously untreated patients with metastatic uveal melanoma. (Funded by Immunocore; ClinicalTrials.gov number, NCT03070392; EudraCT number, 2015-003153-18.)
Gesehen am 28.04.2022